Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M210 - Borowski, Christian; Bach, Alissa; Wölfl, Anne-Cathrin (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M210 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 29.04.2025 - 26.05.2025 from Ponta Delgada (Azores) - Las Palmas (Spain) in the North Atlantic. The cruise M209 aimed to investigate the diversity of hydrothermal fluids at major vent fields and their smaller satellite vents, study the underlying geological processes shaping this diversity, and examine the resulting chemical and microbial diversity at the vents and in the hydrothermal plumes. The focus was on key study sites between 36°N and 38°N, including the major Rainbow and Menez Gwen vent fields, the recently discovered Pit vents near Rainbow, and Capelinhos (a satellite vent of the Lucky Strike hydrothermal vent complex). Data were recorded within the EEZs of Cape Verde. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by Max Planck Institute for Marine Microbiology, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam Echosounder